Konstruksi ilmu pengetahuan dalam pendidikan Islam aliran empirisme, rasionalisme, positivisme, dan idealisme di era kontemporer - Gusli, Ramadhoni Aulia; Ahida, Ridha (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
This paper aims to examine the construction of knowledge in Islamic education with a focus on four philosophical schools of thought, namely empiricism, rationalism, positivism, and idealism. The research was conducted using a qualitative approach with a literature review method, using scientific sources from indexed international journals and academic literature related to the integration of Islamic education. The results of the study show that each epistemological school of thought has a unique contribution that complements each other in the development of the Islamic education system. Empiricism emphasises the importance of learning based on real experiences, rationalism reinforces the tradition of critical and logical thinking, positivism provides a research methodology framework based on evidence, while idealism directs education towards the achievement of transcendental goals in the form of developing knowledgeable and moral individuals. The integration of these four perspectives places revelation as the normative foundation that guides reason, experience, and scientific approaches in the educational process. Through this integrative framework, Islamic education is expected to produce students with not only high intellectual abilities, but also balanced moral, spiritual, and social qualities. The practical implications of this research emphasise the need for a curriculum design oriented towards “ilm al-nāfi”, the enhancement of multidisciplinary professionalism among educators, and the strengthening of epistemic digital literacy so that students are able to respond to global challenges and the rapid flow of information in the modern era. Thus, it is believed that Islamic education can become more adaptive, critical, and relevant in building a fair and characterful contemporary civilisation. Abstrak Tulisan ini bertujuan untuk mengkaji konstruksi ilmu pengetahuan dalam pendidikan Islam dengan fokus pada empat aliran filsafat yaitu empirisme, rasionalisme, positivisme, dan idealisme. Penelitian dilakukan melalui pendekatan kualitatif dengan metode studi pustaka, menggunakan sumber-sumber ilmiah dari jurnal internasional ter indeks serta literatur akademik terkait integrasi pendidikan Islam. Hasil kajian memperlihatkan bahwa masing-masing aliran epistemologi memiliki kontribusi khas yang saling melengkapi dalam pengembangan sistem pendidikan Islam. Empirisme menekankan pentingnya pembelajaran berbasis pengalaman nyata, rasionalisme menguatkan tradisi berpikir kritis dan logis, positivisme menghadirkan kerangka metodologi penelitian yang berbasis bukti, sementara idealisme mengarahkan pendidikan pada pencapaian tujuan transendental berupa pembentukan insan kamil yang berilmu dan berakhlak. Integrasi keempat perspektif tersebut menempatkan wahyu sebagai landasan normatif yang mengarahkan akal, pengalaman, dan pendekatan ilmiah dalam proses pendidikan. Melalui kerangka integratif ini, pendidikan Islam diharapkan tidak hanya melahirkan peserta didik dengan kemampuan intelektual tinggi, tetapi juga dengan kualitas moral, spiritual, dan sosial yang seimbang. Implikasi praktis dari penelitian ini menegaskan perlunya desain kurikulum yang berorientasi pada ‘ilm al-nāfi’, peningkatan profesionalisme pendidik yang multidisipliner, serta penguatan literasi digital epistemik agar peserta didik mampu merespons tantangan global dan derasnya informasi di era modern. Dengan demikian, diyakini mampu menjadikan pendidikan Islam lebih adaptif, kritis, dan relevan dalam membangun peradaban kontemporer yang adil dan berkarakter.